PERTUKARAN SOSIAL DAN REPRODUKSI SOLIDARITAS DALAM TRADISI NARIK WIRIT - Ismail, Ismail (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
The wrist-pulling tradition is a social exchange practice based on a reciprocal system. The research aims to analyze the mechanisms of social exchange in the wrist-pulling tradition in Punggulan village using George C. Homans' theoretical framework. This research uses a qualitative approach with an ethnographic method conducted in Punggulan Village, Air Joman District, Asahan Regency, for two months. Data was collected through participant observation, in-depth interviews with 6 informants (Mrs. Pawit, Sari Rahayu, Mrs. Ayat, and 3 other residents) selected through purposive sampling, as well as documentation. The analysis uses the Miles and Huberman model integrated with seven propositions from Homans' theory. The results of this study indicate that the traditional practice of "narik wirit" is triggered by economic factors and social norms. This tradition also provides financial benefits, social support, and a mechanism for reproducing solidarity through "rewang" (mutual aid). Nevertheless, there is social pressure to reciprocate invitations when pulling rank, even though the economy is struggling. Economically, the benefits felt by the community when pulling wirit are greater than the costs incurred. Additionally, the community also views pulling the wirit as a symbol of social solidarity among residents. Then, intergenerational value differences were found, where the older generation viewed tradition as an obligation of solidarity, while the younger generation saw it as a social debt. The tradition of "narik wirit" demonstrates a balance between economic rationality and social solidarity, with value adaptations aligned with modernization.